Economic growth and its components in south America: Performance in the period 1950-2019 - Angelo Diomar Villalobos Valencia; Leobaldo Enrique Molero Oliva; Alberto Gregorio Castellano Montiel (Revista de Ciencias Sociales, 2023)
The objective of this research was to describe the performance of economic growth and its components in the South American region during the period 1950-2019. The research was descriptive in nature under a quantitative approach, with data from secondary sources covering the period in question. The behavior of the main variables associated with growth, such as Gross Domestic Product and the productive inputs capital and labor adjusted for human capital, were described for the period under study. The results obtained show that economic growth has been relatively modest since the early 1970s. However, in recent years, several countries in the region have made considerable progress in terms of growth of Gross Domestic Product per capita.